2018
DOI: 10.1002/clc.23099
|View full text |Cite
|
Sign up to set email alerts
|

Troponin‐I levels as a potential prognostic biomarker of sacubitril/valsartan treatment response in heart failure with reduced ejection fraction: Who will benefit most?

Abstract: Background Despite robust data on the benefits of sacubitril/valsartan (LCZ696) in patients with chronic heart failure with reduced ejection fraction (HFrEF), there is no evidence yet on prespecified predictive markers of its efficacy. Hypothesis The objective of this study was to identify potential prognostic factors of LCZ696 treatment response. Methods We included 48 symptomatic patients with chronic HFrEF (left ventricular ejection fraction ≤35%) and New York Heart Association (NYHA) class II/III: Group A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The mean follow‐up duration ranged from 3 to 17.1 months. Of the 10 included studies, 6 13 , 15 , 22 , 23 , 24 , 25 were prospective, and 4 14 , 26 , 27 , 28 were retrospective. One study 24 had a control group that received angiotensin‐converting enzyme inhibitor, whereas the others had no control group.…”
Section: Resultsmentioning
confidence: 99%
“…The mean follow‐up duration ranged from 3 to 17.1 months. Of the 10 included studies, 6 13 , 15 , 22 , 23 , 24 , 25 were prospective, and 4 14 , 26 , 27 , 28 were retrospective. One study 24 had a control group that received angiotensin‐converting enzyme inhibitor, whereas the others had no control group.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies have indicated possible predictors for a favorable response to SV in ambulatory patients with HF ( Martens et al, 2018 ; Nakou et al, 2018 ; Vicent et al, 2019 ; Chang et al, 2020 ; Díez-Villanueva et al, 2020 ) ( Table 4 ). These are observational cohort studies, most reflecting single-center experiences, and with a follow-up of less than 1 year after the start of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies agreed that higher doses of SV were more likely to observe a favorable response ( Martens et al, 2018 ; Chang et al, 2020 ). Other predictors proposed were female sex ( Vicent et al, 2019 ), the absence of an ICD ( Díez-Villanueva et al, 2020 ), the non-ischemic etiology of HF ( Chang et al, 2020 ), the smaller diameter of the LV ( Chang et al, 2020 ), and the plasmatic levels of troponin ( Nakou et al, 2018 ). In this regard, our study coincides in that women were significantly more frequent “super-responders” than men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevation of troponin is a very frequent finding in patients hospitalized for acute decompensated HF and is associated with poor outcomes during hospitalization and increased risk of death or rehospitalizations after discharge [19]. Nakou et al [20] already showed that troponin I concentrations may be an independent predictive marker of a sacubitril/ /valsartan positive response in HFrEF.…”
Section: Timementioning
confidence: 99%